Ultrathin (0 0 1) and (1 0 0) TiO2(B) sheets: surface reactivity and structural properties - Fernández Werner, Luciana (2013)
B polymorph of titanium dioxide (TiO2(B)) appears as a metastable phase during thermal annealing of low content sodium layered titanate nanostructures obtained via the widely used hydrothermal synthesis. In addition, the computed formation energy for the TiO2(B) (0 0 1) slabs in the order of the one calculated for anatase (1 0 1) which represents one of the most stable TiO2 surfaces. This encourages the study of this polymorph which could gain prominence in TiO2 applications at the nanoscale. In a first instance ultrathin TiO2(B) sheets, parallel to crystallographic planes (0 0 1) and (1 0 0), are investigated and compared to other well know TiO2 polymorphs, such as rutile and anatase surfaces. Then the adsorption of formic acid on (0 0 1) and (1 0 0) – less stable – TiO2(B) dry ultrathin sheets was studied as the first step for further evaluation of TiO2(B) nanostructures for dye sensitized solar cells (DSSC) applications. The results show that the monodentate through the carbonyl group configuration is the most stable for (0 0 1) sheet while bidentate dissociated configuration is the most stable for (1 0 0) sheet being the computed adsorption energies 0.51 eV and 1.49 eV, respectively. The evaluated reactivity of TiO2(B) slabs is comparable with anatase and indicates that it could be a good adsorbent for common dyes used for dye sensitized solar cells purposes.